Pengaruh Messenger, Message, dan Environtment Dalam Affiliate Marketing Terhadap Impulse Buying Pada Produk Fashion And Beauty di Platform Tiktok - Agnesia Gian Marcheren; Lie Othman (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The purpose of this study is to determine the influence of dimensions affiliate marketing (messenger, message, And environment) to behaviorimpulse buyingstudents on the productfashion and beauty Of platformTikTok. The research method used was a quantitative explanatory method, with data collection techniques in the form of a questionnaire answered by 96 respondents. Respondents were determined using the techniquepurposive samplingThis study uses analysis such as validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test and coefficient of determination test (R2).2). Based on the analysis that has been carried out, the results obtained are thatmessenger, message, And environmenthas a positive and significant effect on impulse buying students on the productfashion and beauty Of platformTikTok partially and simultaneously